Utilization of Rainwater into Fresh Water through Electrolysis Method for Communities Affected by Tidal Flooding - Qudus, Nur; Harianingsih, Harianingsih; Sugiyarto, Bambang; Kristianto, Virgiawan Adi; Siswoyo, Mohammad Pujo; Pangestu, Indra Sakti; Erliana, Savira Rinda; Ubay, Isnina Noor (Universitas Negeri Semarang, 2024)
Water is an essential resource, crucial for human survival and well-being. In coastal areas like Sayung District, Demak Regency, Central Java, accessing clean drinking water is a significant challenge. This problem is made worse by environmental issues such as tidal flooding, known locally as